ChemInform Abstract: Direct gem‐Difluoromethylenation of sp3‐Hybridized Carbon Center Through Copper‐Mediated Radical/Radical Cross‐Coupling for the Construction of a CH2—CF2 Linkage. Issue 9 (February 2016) - Jiang, Haizhen; Xu, Minjun; Lu, Wenjun; Tian, Wenfeng; Wan, Wen; Chen, Yunrong; Deng, Hongmei; Wu, Shaoxiong; Hao, Jian
Abstract: The title reaction between various benzyl bromides and benzo‐1, 3‐oxazolic difluoromethyl bromides tolerates various functional groups and proceeds in generally high yields.